2013
DOI: 10.1038/nature12879
|View full text |Cite
|
Sign up to set email alerts
|

Patterning and growth control by membrane-tethered Wingless

Abstract: Wnts are evolutionarily conserved secreted signalling proteins that, in various developmental contexts, spread from their site of synthesis to form a gradient and activate target-gene expression at a distance. However, the requirement for Wnts to spread has never been directly tested. Here we used genome engineering to replace the endogenous wingless gene, which encodes the main Drosophila Wnt, with one that expresses a membrane-tethered form of the protein. Surprisingly, the resulting flies were viable and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
326
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(348 citation statements)
references
References 39 publications
18
326
2
Order By: Relevance
“…Despite abundant genetic evidence that Wg signalling promotes stem cell proliferation in flies (Lin et al , 2008; Cordero et al , 2012; Tian et al , 2016), the source of Wg has remained unclear. Using new, improved tools to visualise Wg expression (Alexandre et al , 2014), our findings lend further support to recent data (Tian et al , 2016) indicating that the source of Wg ligand is not the stem cells themselves, despite the striking Ret‐driven upregulation of Wg on their surface. How might Ret signalling in adult intestinal progenitors lead to Wg protein upregulation in these cells without affecting its transcript?…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Despite abundant genetic evidence that Wg signalling promotes stem cell proliferation in flies (Lin et al , 2008; Cordero et al , 2012; Tian et al , 2016), the source of Wg has remained unclear. Using new, improved tools to visualise Wg expression (Alexandre et al , 2014), our findings lend further support to recent data (Tian et al , 2016) indicating that the source of Wg ligand is not the stem cells themselves, despite the striking Ret‐driven upregulation of Wg on their surface. How might Ret signalling in adult intestinal progenitors lead to Wg protein upregulation in these cells without affecting its transcript?…”
Section: Discussionsupporting
confidence: 87%
“…This suggested that the increased Wg protein observed following Ret expression may result from a non‐transcriptional mechanism. To confirm this, we analysed wg transcription with cell specificity by making use of wg KO ‐Gal4 : a wg transcription reporter in which Gal4 is expressed under the control of the endogenous wg promoter (Alexandre et al , 2014). As described in a previous study (Tian et al , 2016), we found no expression of this reporter in adult intestinal stem cells (Fig 3E), but were able to detect it at intestinal compartment boundaries (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocytosis also mediates Arrow-directed degradation necessary for the observed Wg distribution and signaling (14). However, rescue of patterning is observed even upon replacement of the endogenous Wg with a transmembrane-tethered Wg, thus raising questions on the importance of a secreted Wg gradient (15). Regardless, inhibition of endocytosis in the recipient cells, by using the dominant-negative (DN) or the temperature-sensitive form of shibire, demonstrates the importance of dynamin-dependent endocytosis in Wg-mediated signaling (11,13).…”
mentioning
confidence: 99%
“…We also looked at flies expressing a membrane-tethered form of Wg (NRT-Wg) from the endogenous wg locus (Alexandre et al, 2015). Anti-Wg again showed high Wg signals at the pylorus, with no obvious signalling gradient ( Figure 1E,E').…”
mentioning
confidence: 99%